Identification and the preliminary in vitro characterization of IRIS homologue from salivary glands of Ixodes persulcatus Schulze - Toyomane, K.; Konnai, S.; Niwa, A.; Githaka, Naftaly W.; Isezaki, M.; Yamada, S.; Ito, T.; Takano, A.; Ando, S.; Kawabata, H.; Murata, S.; Ohashi, K. (Elsevier, 2016)
Ixodes ricinus immunosuppressor (Iris) is a tick salivary gland protein derived from I. ricinus. In this study, Iris homolog was identified in the salivary glands of Ixodes persulcatus, which is the specific vector of the Lyme disease agent in Japan. The homolog was named Ipis-1. To investigate the function of Ipis-1, we prepared a recombinant Ipis-1 expressed in COS-7 cells as a rabbit IgG Fc-fused protein (Ipis-1-Ig). Cell proliferation assay and IFN-γ ELISA showed that Ipis-1-Ig inhibits the proliferation and IFN-γ production of bovine peripheral blood mononuclear cells (PBMCs). Notably, Ipis-1-Ig inhibited the cell proliferation and production of IFN-γ in bovine PBMCs even when CD14+ cells were depleted, suggesting that Ipis could directly interact with T cells and inhibit their functions. In conclusion, Ipis could contribute to the establishment of environments suitable for tick blood feeding and pathogen transmission by suppressing the function of immune cells.